Preparation and characterization of nigella sative microemulsions - Mohd Nor, Nor Hafizah; Mohd Shafri, Mohd Affendi; Mohamed, Farahidah (Academic Sciences, 2014)
The aims of this study were to develop and characterize an oil-in-water (o/w) Nigella sativa (N. sativa) microemulsion. The microemulsions were prepared by drop-wise titration of N. sativa oil into mixtures of surfactant blends (Span 20, Span 80, Tween 20, Tween 80, Tween 85) and water. All transparent ternary mixtures were characterized for their viscosity and droplet size. The stability of the microemulsion was evaluated by subjecting them to stressful conditions, namely centrifugation (2000 g for 20 minutes) and heating in a drying oven (60 °C to 105 °C for 5 hours) and the droplet size was determined following one month storage at room temperature (25 °C) thereafter. Based on the results, a phase diagram was constructed from corresponding volumes of those 3 components. N. sativa mixtures (ranging from 7.4% to 10.7%) prepared at HLB 16 of surfactant blends (Tween 20: Tween 80; 6:4) with water (ranging from 17.9% to 18.5%) yielded transparent liquids. The constructed phase diagram displayed regions of a few types of microemulsion and emulsion. Interestingly, droplet size of freshly prepared mixtures was wider in range (5 to 15.6 nm) than the size following stressful condition (11.3 to 12.4 nm). It was concluded that N. sativa oil could be formulated into microemulsion at specific HLB value of surfactant blends. Such system was envisaged to enable routine rapid in vitro test on neuron cell lines loaded with N. sativa oil or possibly other lipophilic materials whenever viewing of neurite extension is required.